Legalitas Peresmian Akta Notaris Berbasis Cyber Notary Melalui Media Konferensi Zoom - Dita Darmaangga, I Dewa Gede Cahaya; Mayasari, I Dewa Ayu Dwi (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 6 No 01 (2021), 2021)
This study aims to find out about the legality of the inauguration of cyber-based notary deeds through the Zoom Conference media and the legal consequences of notarial deeds inaugurating the Zoom Conference media. The research method used is normative legal research methods that use a statutory approach and analysis of legal concepts based on primary and secondary legal materials. The study result show that according to Article 1868 of the Civil Code stipulates that the making of an authentic deeds is made is the presence of an authorized public official. Homeever, when referring to the explanation of Article 15 paragraph (3) of Law Number 2 of 2014 concerning the Position of Notary Public, there is no clarity regarding the explanation regarding electronic certification (cyber notary) whether tappers must remain physically present in front of a notary or may not ignore it virtually. Regarding the inauguration of deeds through the Zoom Conference media, its is necessary to have clearer regulations regarding the concept of cyber notary in the world of notary so that notaries can carry out their duties without violating laws and regulations. The concept of cyber notary, in the inauguration of the deed, it is felt that there is a need for regulations that clearly regulate how the terms or conditions in the inauguration of authentic deeds/notaries are carried out using the concept of cyber notary, one of which is the Zoom Cenference media.   Studi ini bertujuan untuk mengetahui mengenai legalitas peresmian akta Notaris berbasis cyber notary melalui media Konferensi Zoom dan akibat hukum peresmian akta otaris dilakukan dengan media Konferensi Zoom . Metode penelitian yang digunakan yaitu dengan metode penelitian hukum normatif yang menggunakan pendekatan perundang-undangan serta analisis konsep hukum dengan bersumber pada bahan-bahan hukum primer maupun sekunder. Hasil studi menunjukan bahwa menurut Pasal 1868 KUHPerdata menentukan mengenai pembuatan akta otentik tersebut dibuat dihadapan pejabat umum yang berwenang. Tetapi apabila merujuk terhadap penjelasan Pasal 15 ayat (3) Undang-Undang Nomor 2 Tahun 2014 Tentang Jabatan Notaris tidak ada kejelasan mengenai penjelasan mengenai sertifikasi elektronik (cyber notary) apakah para penghadap harus tetap hadir secara fisik dihadapan notaris ataukah boleh tidak melaikan secara virtual. Terkait dengan peresmian akta melalui media Konferensi Zoom maka diperlukan adanya pengaturan lebih jelas mengenai konsep cyber notary dalam dunia kenotariatan agar notaris dapat menjalankan tugas jabatannya tanpa menyalahi undang-undang dan peraturan perundang-undangan. Konsep cyber notary ini dalam peresmian akta dirasa perlunya ada pengaturan yang mengatur dengan jelas bagaimana ketentuan atau syarat dalam peresmian akta autentik/notaris yang dilakukan dengan menggunakan konsep cyber notary salah satunya adalah media Konferensi Zoom.